2015
DOI: 10.3928/01477447-20150902-57
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment for Central Calcified Thoracic Disk Herniation: A Novel L-Shaped Osteotome

Abstract: Few reports are available on the posterior transfacet approach for the treatment of central calcified thoracic disk herniation (TDH). The objective of this study was to assess outcomes and complications in a consecutive series of patients with TDH who underwent posterior transfacet decompression and diskectomy with segmental instrumentation and fusion. The data for 27 patients (16 males and 11 females) were retrospectively reviewed and analyzed, including clinical presentation, blood loss, operative time, pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
0
9
0
1
Order By: Relevance
“…TTIF yielded good outcome in other series as well (n ¼ 18, n ¼ 11, n ¼ 27, n ¼ 25, n ¼ 51) with minor or major complication rate of 33%, 18%, 3.70%, 12%, and 1.96% respectively. 8,10,[15][16][17] No deterioration due to cord handling noted in these series. No anticoagulants were given by us.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…TTIF yielded good outcome in other series as well (n ¼ 18, n ¼ 11, n ¼ 27, n ¼ 25, n ¼ 51) with minor or major complication rate of 33%, 18%, 3.70%, 12%, and 1.96% respectively. 8,10,[15][16][17] No deterioration due to cord handling noted in these series. No anticoagulants were given by us.…”
Section: Discussionmentioning
confidence: 62%
“… 9 However, posterior approach decompression with or without fusion has been advocated as an alternative and successful treatment modality in other reports. 10 17 One of the main problems is that an accomplished spine surgeon will see very low numbers of TDP in his life time. This makes long series reporting less likely.…”
Section: Introductionmentioning
confidence: 99%
“…Авторы публикаций, посвященных заднему доступу, видят его преиму-щество не только в меньшей частоте осложнений, но и в лучшей возможности контролировать эпидуральное пространство, его венозные сосуды и состояние твердой мозговой оболочки [7,19,22]. Разнообразие задних доступов расширяет возможности их применения и позволяет удалять не только мягкотканные латерально расположенные, но и медиальные оссифицированные грыжи диска [7,8,20,21,22,25]. Coppes et al [21], удалив 13 грыж из заднего трансдурального доступа, получили благоприятные результаты во всех наблюдениях.…”
Section: отбор публикаций для обзораunclassified
“…While the need for a surgical procedure is commonly accepted in cases of symptomatic hernia with a sign of myelopathy, the medical management of cases with an asymptomatic or only slightly symptomatic lesion may be debated, especially if the lesion is voluminous, since the risk associated with an intervention is not negligible, ranging from 3.7% to 66.6% of complications in the most recent series [4][5][6][7][8][9]. A study of the literature on significant TDH (>20% of the spinal canal) revealed a small number of case reports noting spontaneous resorption [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%